Association of allergic diseases with children's life satisfaction: population-based study in Finland. Issue 3 (30th March 2018) - Haanpää, Leena; af Ursin, Piia; Nermes, Merja; Kaljonen, Anne; Isolauri, Erika
Abstract : Objective: To assess the impact of allergic diseases on the subjective well-being and life satisfaction of primary-school children. Design: Population-based cohort. Setting: Finnish sample of children ages 10 and 12 from the International Survey of Children's Well-Being. Participants: Nationally representative sample of 1947 school children. Main outcome measure: Two different instruments to assess the child's own perception of well-being, the short version of the Student Life Satisfaction Scale (SLSS) and the Brief Multidimensional Student Life Satisfaction Scale (BMSLSS). Results: Altogether, 51.4% of children reported having at least one allergic condition (10.1% asthma, 23.8% eczema and 40.3% seasonal allergic rhinitis). A statistically significant distinction in life satisfaction emerged between non-allergic and allergic children (inferior in the latter). In particular, children with eczema were more likely to report a reduction in life satisfaction compared with non-allergic children (SLSS β=−128.220; BMSLSS β=−90.694; p<0.01). Apart from freedom from eczema, good life satisfaction was associated with a physically active lifestyle. Conclusions: Active allergic disease reduces the child's own perception of well-being. During clinical visits, more attention should be paid to the child's psychosocial status and impairments, which may differ substantially from those of parents or medical authorities.